Observational study on the eating behavior of a heterogeneous group of young athletes - Alisia D'Angelo; Martina Di Berardino; Alessio Matarazzo; Oriana Forte; Antonella Fondi; Gabriella Di Giacinto; Patrizio Ripari (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2023)
Eating Disorders represent one of the fastest-growing mental health problems in the world. While a diagnosis of an eating disorder can only be made after careful psychiatric evaluation, the detection of "at-risk" individuals can be conducted through screening programs that use tools such as the Eating Attitude Test (EAT-26), a test used to measure the symptoms and concerns characteristic of eating disorders. This observational study was designed to evaluate the presence of at-risk individuals, using the EAT-26, among young athletes in "lean sports", young athletes in non-"lean sports", young non-athlete sportspeople, and young people who did not practice any sports. In addition, the presence of a correlation between the risk of developing eating disorders, gender, and age was also investigated. The results identified a prevalence of risk of 13% among study participants. None of the subjects who did not engage in any physical activity obtained a test score that could be considered at risk. Furthermore, no correlation was found between gender and the scores obtained. These results should be taken into consideration to emphasize the importance of nutritional intervention by expert and qualified personnel within various sports societies, in order to prevent the development of these pathologies and at the same time increase and improve performance.